Herpes simplex type 2 infection in a cohort aged 21 years. Issue 3 (June 1998) - Eberhart-Phillips, J; Dickson, N P; Paul, C; Fawcett, J P; Holland, D; Taylor, J; Cunningham, A L
Abstract : OBJECTIVES: To measure the prevalence of HSV-2 antibodies in a birth cohort of 21 year old New Zealanders from whom detailed sexual histories had been obtained, and to assess the potential for HSV-2 serology in characterising a young adult population's risk for sexually transmitted diseases (STD). METHODS: Sera from 784 cohort members were tested using an indirect IgG enzyme linked immunoassay specific to the HSV-2 glycoprotein G. Positive results were confirmed by western blot. RESULTS: In all, 27 subjects were seropositive for HSV-2 (3.4%), only seven of whom gave a history of genital herpes (26%). Risk among females increased with lifetime number of partners, while risk for males increased with having a first partner who was aged 16 years or under. CONCLUSIONS: The seroprevalence of HSV-2 infection in this cohort was low, but similar to that seen in several other populations in this age group. HSV-2 seropositivity did not appear to be a sensitive marker for high risk sexual activity in this young population. This may be because a critical mass of HSV-2 carriers has not accumulated among potential partners by age 21 years.